The effects of situational teaching, cooperative learning, and self-directed learning on mathematical learning abilities in China - Chen, Lei; Razali, Fazilah (Macrothink Institute, 2021)
The junior high school stage is a significant stage of education because students thinking skills develop the fastest in junior middle school. In addition, the quality of junior high school education impacts the students learning ability, especially in mathematics, and the teaching methods also play a key role in students' mathematical learning ability. Therefore, this research explores the impact of problem-based learning on junior high school students’ mathematical learning ability, and studies their impact on students’ mathematical learning ability from the core principles of problem-based learning, including learning situations, cooperative learning, and self-directed learning. A total of 240 students from Meixi Lake Changjun Middle School participated in this research based on quantitative research methods collected of such as the "Mathematical Ability Scale" and other questionnaires. The correlation analysis revealed that situational teaching, self-directed learning and cooperative learning have a moderately positive correlation with students’ mathematical abilities. In this study, an independent sample t-test analyzed the significant correlation between gender and mathematical learning abilities. This research aims to find better learning methods to improve the mathematical learning abilities of Chinese junior high school students and their performance in mathematics subjects.